Exploring the Driving Factors for Low-Carbon Development of the Construction Industry in China - Yiyu Geng; Youquan Xu; Ke Ma; Yuanyuan Li; Zhigang Zhang (Buildings)
The construction sector in China exhibits elevated levels of energy consumption and carbon emissions, which presents considerable obstacles to the attainment of carbon reduction objectives. Contemporary research predominantly focuses on the advancement of low-carbon building technologies and the measurement of carbon emissions. This study seeks to study the driving factors of low-carbon development in China’s construction industry and the complex relationships between different entities from the perspective of industrial systems. Initially, through a comprehensive literature review and expert interviews, six distinct stakeholders and twenty-one relevant driving factors were identified. Following this, Social Network Analysis was employed to evaluate the data collected from the surveys. The findings suggest that ten critical factors, such as the market demand for emerging market entities, the market demand and competition for construction entities, and business needs for non-governmental entities, significantly influence the low-carbon construction industry. Within the network of participants, the government, the public, and construction entities are positioned centrally, exerting substantial influence and emerging as focal points for industrial development. The insights derived from this study will provide critical guidance on the engagement of various stakeholders in low-carbon initiatives and will serve as a reference for policymakers in the transformation of the construction industry.